.3x+1.7=.2x-.4(5x+1)

Simple and best practice solution for .3x+1.7=.2x-.4(5x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .3x+1.7=.2x-.4(5x+1) equation:


Simplifying
0.3x + 1.7 = 0.2x + -0.4(5x + 1)

Reorder the terms:
1.7 + 0.3x = 0.2x + -0.4(5x + 1)

Reorder the terms:
1.7 + 0.3x = 0.2x + -0.4(1 + 5x)
1.7 + 0.3x = 0.2x + (1 * -0.4 + 5x * -0.4)
1.7 + 0.3x = 0.2x + (-0.4 + -2x)

Reorder the terms:
1.7 + 0.3x = -0.4 + 0.2x + -2x

Combine like terms: 0.2x + -2x = -1.8x
1.7 + 0.3x = -0.4 + -1.8x

Solving
1.7 + 0.3x = -0.4 + -1.8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.8x' to each side of the equation.
1.7 + 0.3x + 1.8x = -0.4 + -1.8x + 1.8x

Combine like terms: 0.3x + 1.8x = 2.1x
1.7 + 2.1x = -0.4 + -1.8x + 1.8x

Combine like terms: -1.8x + 1.8x = 0.0
1.7 + 2.1x = -0.4 + 0.0
1.7 + 2.1x = -0.4

Add '-1.7' to each side of the equation.
1.7 + -1.7 + 2.1x = -0.4 + -1.7

Combine like terms: 1.7 + -1.7 = 0.0
0.0 + 2.1x = -0.4 + -1.7
2.1x = -0.4 + -1.7

Combine like terms: -0.4 + -1.7 = -2.1
2.1x = -2.1

Divide each side by '2.1'.
x = -1

Simplifying
x = -1

See similar equations:

| 5c/3c-1 | | 2x+6/x-9=0 | | 8x^2-38x-10=0 | | .3(x-2)+.4x=.2(x-6) | | 2(x-4)=5/6(x+6)-6 | | 3x-23=97-9x | | 1/5(y+2)=1/10y+3/5 | | 2x-4+7=-6x+41 | | 3x-2(x-4)=8-2x+15 | | -3-4x=5x+24 | | 5-(1/2)x=(1/8)x | | 5x^2-4x+3=6 | | 11c=9c+14 | | 2-2x-5/5=x+9/4 | | 12x-3x-7=11 | | 56-s=45-9 | | 1+(3*7)=z | | 1+(3*7)= | | 1/2-1=1/44 | | -24p^2q^2+(-2pq)+3= | | 2x-6x+21=-13 | | -4x+21=-13 | | 28x+4+7x+7=102 | | 1xy=78 | | 1*y=787 | | 1y=78 | | xy=-40 | | ax+5x-4=10 | | 4-4x^2+4xy-y^2= | | 15-1/2x=1/4x | | x/5-x/3=8/15 | | 5/8+(-7/12) |

Equations solver categories